2014
DOI: 10.1039/c4ra10150b
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide incorporated collagen–fibrin biofilm as a wound dressing material

Abstract: GO was incorporated in the collagen and fibrin composite film (CFGO), these films were used as wound dressing material on the experimental wounds of rats and the efficacy of CFGO was studied using conventional methods (schematic illustration).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 55 publications
0
38
0
Order By: Relevance
“…For GO flakes, peaks at 1054 cm −1 were related to the alkoxy group, and those at 1620 and 1728 cm −1 were both attributed to the carboxyl group (COOH) . Infra‐red spectra of the Col scaffold showed amide I, II, III, and A group peaks at 1645, 1549, 1243, and 3315 cm −1 , respectively . For the Col–GO‐90 scaffold, the presence of alkoxy groups was identified by a peak at 1046 cm −1 and the detection of amide groups was also confirmed by observing the related peaks mentioned above.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…For GO flakes, peaks at 1054 cm −1 were related to the alkoxy group, and those at 1620 and 1728 cm −1 were both attributed to the carboxyl group (COOH) . Infra‐red spectra of the Col scaffold showed amide I, II, III, and A group peaks at 1645, 1549, 1243, and 3315 cm −1 , respectively . For the Col–GO‐90 scaffold, the presence of alkoxy groups was identified by a peak at 1046 cm −1 and the detection of amide groups was also confirmed by observing the related peaks mentioned above.…”
Section: Resultsmentioning
confidence: 87%
“…Figure shows the FT‐IR spectra of GO flakes, Col, and Col–GO‐90 scaffolds with the corresponding reduced sample. For GO flakes, peaks at 1054 cm −1 were related to the alkoxy group, and those at 1620 and 1728 cm −1 were both attributed to the carboxyl group (COOH) . Infra‐red spectra of the Col scaffold showed amide I, II, III, and A group peaks at 1645, 1549, 1243, and 3315 cm −1 , respectively .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a related application, collagen-fi brin (CF) biocomposite fi lms incorporated with GO (CFGO) were prepared for would healing. [ 159 ] The existence of GO enhanced the mechanical strength of collagen/fi brin fi lms. Faster wound healing was found in CFGO treated rats compared with those without GO, which indicated that graphene-based materials enhanced wound healing and might be used on more clinical wounds of various animal models before their applications on human beings.…”
Section: Skin Regenerationmentioning
confidence: 99%
“…Wound dressings prepared from sodium carboxymethyl cellulose and rGO reduced biofilm formation caused by S. aureus and P. aeruginosa significantly in vitro . Collagen–fibrin composite films incorporated with GO were biocompatible and enhanced wound healing . Furthermore, the application of metal‐based NPs in wound dressings has been reported to prevent the wound from bacterial infections.…”
Section: Introductionmentioning
confidence: 99%